Effect of Different Lower Limb Stretching Exercises on Flexibility among Table Tennis Players - Khatri, Rajendra; Maharjan, Kabita (Journey for Sustainable Development and Peace Journal, 2025)
This research aims to examine the effectiveness of Sit-and-reach flexibility on lower limbs in table tennis players. An experimental study was conducted to evaluate the impact of lower limb exercises on flexibility among 35 school-aged table tennis players at the Adarsha Vidhaya Mandir Table Tennis Club in two phases: pre-phase(before training of Sit-and-reach for flexibility) and post-phase (after training). Data were analyzed using paired sample tests between pre and post-phases. The finding suggests that regular lower limb stretching significantly improves flexibility in table tennis players, which in turn enhances performance and reduces the risk of injury. The sit and reach test shows that the mean test differs before stretching (M=17.60, SD=9.076) and after stretching exercise (M=20.31, SD=8.014) at the 0.05 level of significance, which demonstrates the effectiveness of the intervention. This research provides valuable insights into the strength of lower limb flexibility in enhancing the performance of table tennis players.